Graphene as a flexible template for controlling magnetic interactions between metal atoms. (12th January 2017) - Lee, Sungwoo; Kim, Dongwook; Robertson, Alex W; Yoon, Euijoon; Hong, Suklyun; Ihm, Jisoon; Yu, Jaejun; Warner, Jamie H; Lee, Gun-Do
Abstract: Metal-doped graphene produces magnetic moments that have potential application in spintronics. Here we use density function theory computational methods to show how the magnetic interaction between metal atoms doped in graphene can be controlled by the degree of flexure in a graphene membrane. Bending graphene by flexing causes the distance between two substitutional Fe atoms covalently bonded in graphene to gradually increase and these results in the magnetic moment disappearing at a critical strain value. At the critical strain, a carbon atom can enter between the two Fe atoms and blocks the interaction between relevant orbitals of Fe atoms to quench the magnetic moment. The control of interactions between doped atoms by exploiting the mechanical flexibility of graphene is a unique approach to manipulating the magnetic properties and opens up new opportunities for mechanical-magnetic 2D device systems.